Considerations in developing and using CAT to assess students' proficiency in English as a foreign language in Indonesia - Ignatius Harjanto; Davy Budiono (Magister Scientiae, 2010)
The English curriculum for Secondary Schools in Indonesia requires the students to acquire ability in accomplishing tasks adequately, to find solutions, and to realize them in real situations. Such objectives can be achieved if, among others, teachers are qualified. This means that the graduates of teacher training colleges (TTCs) must be competent in the field having knowledge and skills. In case of English education, they must be proficient in the four English skills. To ensure their English proficiency, a test administered institutionally, which varies from one college to another, is not enough. A national test on English proficiency to the graduating students of TTCs is needed so that a national standard of proficiency for teachers can be measured. However, administering a national English proficiency test is expensive and cumbersome as well. A solution to the problem is the application of computer adaptive tests (CAT). This article argues that CAT enables the students to measure their own level of English proficiency inexpensively. Ideas on the rationale, application, and impacts of standardized proficiency test using CAT on students with learning English difficulties in regular schools are shared.